Double emulsions with controlled morphology by microgel scaffolding - Thiele, Julian; Seiffert, Sebastian (Lab on a chip, 2011)
Double emulsions are valuable structures that consist of drops nested inside bigger drops; they can be formed with exquisite control through the use of droplet-based microfluidics, allowing their size, composition, and monodispersity to be tailored. However, only little control can be exerted on the morphology of double emulsions in their equilibrium state, because they are deformable and subject to thermal fluctuations. To introduce such control, we use droplet-based microfluidics to form oil-in-water-in-oil double emulsion drops and arrest their shape by loading them with monodisperse microgel particles. These particles push the inner oil drop to the edge of the aqueous shell drop such that the double emulsions adopt a uniform arrested, anisotropic shape. This approach circumvents the need for ultrafast polymerization or geometric confinement to lock such non-spherical and anisotropic droplet morphologies. To demonstrate the utility of this technique, we apply it to synthesize anisotropic and non-spherical polyacrylate-polyacrylamide microparticles with controlled size and shape.